The Impact of Price and Service Quality on Purchase Decision at Mitra Jaya Mandiri - Nisrina Audya Putri; Budi Prasetiyo (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the effect of price and service quality on purchase decision at Mitra Jaya Mandiri, a textile Small and Medium Industries (SMI) in Majalaya, West Java, Indonesia. Research Methodology: This study used a quantitative method with a descriptive and causal approach. Data from 83 respondents were collected through purposive sampling and analyzed using multiple linear regression with IBM SPSS (version 29). Results: All variables fell into the very good category. Price positively and significantly influenced purchase decisions partially, as did service quality. Simultaneously, these two variables also have a significant impact, with an adjusted R² of 0.620, explaining 62% of the variance in purchase decisions. Conclusions: Price and service quality positively and significantly influenced purchase decisions at Mitra Jaya Mandiri, both individually and collectively. Therefore, companies are advised to improve their price competitiveness and packaging standards to better meet customer expectations and enhance sales performance. Limitations: This study is confined to customers of one company in 2025, with only two variables examined under a cross-sectional design. Contributions: This study adds empirical evidence on the influence of price and service quality on purchase decisions in the textile SMI sector in Majalaya. The findings indicate that service quality has a stronger influence than price, offering practical insights for SMI practitioners.